Washington View: More research could improve policies. (December 2014) - Ferguson, Maria
Ideally, education policy would be informed by evidence-based research results. But the realms and ways of education researchers and education policy makers are incongruent. Policy makers can't wait for decade-long research to conclude before political realities force their hands, and the research community wants its product to be separate from politics. But this makes it even more important that the U.S. expand its education research apparatus to better inform policy decisions.